2022
DOI: 10.1037/pha0000480
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with alcohol and drug use among bisexual women: A literature review.

Abstract: Bisexual women report elevated alcohol and drug use compared to other sexual minority women. This review summarized extant research on mechanisms (i.e., coping processes with minority stress and victimization, disclosure of sexual identity, connectedness to lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQ+) community, religiosity, and normative perceptions) that may influence alcohol and other drug use among bisexual women. Specifically, bisexual women experience unique sexual discrimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 120 publications
0
11
0
Order By: Relevance
“…Thus, interventions could assess binegativity to identify bisexual women at greatest risk for negative health outcomes. 6…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, interventions could assess binegativity to identify bisexual women at greatest risk for negative health outcomes. 6…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Extant literature suggests that among bisexual women, specifically, impulsive tendencies may associate with heightened drinking motivations and greater risk for alcohol-related problems. 6 For example, one cross-sectional study found that impulsivity moderated the relationship between drinking-to-cope motivations and alcohol-related problems among a sample of bisexual women. 8 That is, although drinking-to-cope motivations were found to positively associate with alcohol-related problems, the relationship was stronger for individuals who demonstrated greater dispositional impulsivity.…”
Section: Impulsivity and Risky Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that religiosity was protective against hazardous drinking and drug use among both SMW and heterosexual women ( Drabble et al, 2016 ). Associations between religiosity and alcohol use may also differ between bisexual and lesbian women ( Schulz et al, 2021 ). One study found that religiosity was protective against heavy episodic drinking among heterosexual women; however, it was not protective for lesbian women and it was associated with increased drinking among bisexual women ( Rostosky et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…When compared to lesbian and heterosexual women, bisexual women have been found to report greater odds of alcohol use, binge drinking, and alcohol-related problems (Schuler & Collins, 2020; Schulz et al, 2021). For example, data from the 2015 to 2017 National Survey on Drug Use and Health revealed that 38.7% of bisexual women reported past month binge drinking and 12.5% were diagnosed with an alcohol use disorder in the past year, which were significantly higher rates as compared to lesbian (binge: 30.1%; alcohol use disorder: 7.7%) and heterosexual (binge: 21.2%; alcohol use disorder: 3.9%) women (Schuler & Collins, 2020).…”
mentioning
confidence: 99%